Improving laboratory test ordering can reduce costs in surgical wards - Giordano, Davide; Zasa, Michele; Iaccarino, Corrado; Vincenti, Vincenzo; Dascola, Isabella; Brevi, Bruno Carlo; Gherli, Tiziano; Raso, Maria Gabriella; Campaniello, Giovanna; Bonelli, Patrizia; Vezzani, Antonella (Acta Biomedica Atenei Parmensis, 2015)
Background and Aim Laboratory blood tests for hospitalized patients are often overused. Excessive costs and no proof of benefit suggest re-evaluating the current approach to laboratory test ordering. The aim of the study is to improve the decision-making process of test ordering and to investigate what effect a rational, evidence-based use of laboratory test ordering in surgical wards would have on costs and healthcare resources. Methods Three-phase experimental prospective study carried out at the tertiary referral teaching hospital of Parma. Phase 1 (baseline status). The baseline status of laboratory test ordering was evaluated by recording the number of biochemical tests requested for patients undergoing elective surgery. Laboratory tests were grouped in “recommended” (RT) and “non recommended” (nRT) tests on the basis of pertinent literature. Phase 2 (improvement action): new guidelines were introduced into clinical practice. Phase 3 (feedback): Prospective data collection for first and second feedback was performed with no advance notice. Results A highly significant reduction in test ordering was found on occasion of the phases 2 and 3 of the study. The overall number of tests decreased, largely due to a decrease in the use of nRT. Conclusions Analysis was justified by the fact that most test requests proved not to be supported by clinical evidence. Inappropriate ordering of laboratory tests results in an unnecessarily high number of requests, which do not in turn improve patient management. Moreover, more appropriate, evidence-based laboratory test ordering for patients undergoing elective surgery may produce a significant reduction in costs, particularly in high-cost settings. (www.actabiomedica.it)